Influence of Meteorological Factors on Varations of Particulate Matter (PM10) Concentration During Haze Episodes in Malaysia. - Nur Izzah Mohamad Hashim (School of Materials Engineering, Universiti Malaysia Perlis, 2017)
It is very important to ensure that this research will contribute to the environmental engineering field of studies. Therefore, this research was carried out with the three main objectives, which are: To study the descriptive statistic of particulate matter (PM10) and weather parameter during haze episodes. To determine the influence between meteorological factors and particulate matter (PM10) concentration during haze episodes. To develop the linear regression models using Multiple Linear Regression (MLR) to predict the concentrations of PM10 and to choose the best model using several performance indicators.